Analysis of Platelet Lymphocyte Ratio on Severe COVID-19 and Dengue Hemorrhagic Fever Grade IV - Verliyanti Verliyanti; Tenri Esa; Asvin Nurulita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Thrombocytopenia can occur in severe COVID-19 or grade IV DHF. In COVID-19, lymphopenia occurs gradually due to Angiotensin Converting Enzyme-2 as the primary response to SARS-CoV-2 and cytokines that can damage lymphocytes.   Contrastingly, lymphocytosis occurs in dengue virus infection. Platelet-to-lymphocyte ratio (PLR) is a new inflammatory marker in predicting the severity of both diseases. This study aimed to analyze differences in PLR values in severe COVID-19 and grade IV DHF and determine the cut-off values. Retrospective research of a cross-sectional approach was carried out using medical record data of patients diagnosed with severe COVID-19 and grade IV DHF by clinicians at Dr. Wahidin Sudirohusodo Hospital from January 2017 to October 2021. The platelet-to-lymphocyte ratio was obtained from the complete blood count results using the flow cytometry method at the beginning of hospitalization. Mann-Whitney test and Receiver Operating Characteristics (ROC) curve were used for statistical analysis. A total of 74 severe COVID-19 and 33 grade IV DHF patients were involved; PRL of severe COVID-19 in dead patients was higher than in recovered patients (p>0.05). The platelet-to-lymphocyte ratio value was significantly lower in grade IV DHF patients who died compared to those who recovered (p<0.001). Platelet to-lymphocyte ratio cut-off of 48.30 for severe COVID-19 was obtained with an Area Under the Curve (AUC) of 0.631 (sensitivity of 54.3%, specificity of 78.6%) and cut-off of 0.715 for grade IV DHF with an AUC of 0.989 (sensitivity of 94.4%, specificity of 100%). There was a difference in PLR value in severe COVID-19 and grade IV DHF. Severe COVID-19 patients who died had higher PLR, whereas grade IV DHF patients had lower PLR values. Values above the PLR cut-off of 48.30 for severe COVID-19 and 0.715 for grade IV DHF can predict the severity of the disease.